More about economic and non-economic determinants of (mutual) trust and trustworthiness - Friedrich L. Sell (Universität der Bundeswehr München, Fachgruppe für Volkswirtschaftslehre, 2007)
The aim of this paper is threefold: we first discuss the appropriateness of the traditional trust-game-tree for the analysis of trust relationships. Following the definition put forward by Lee et al. (2005) that confident expectations and a willingness to be vulnerable are critical components of all definitions of trust, we relate these criteria to the subjective probabilities given by Coleman's inequality. Then, we develop the trust-tree-game further to a psychological trust game in the vein of Dufwenberg (2002). Here, we complement the concept of trust responsiveness with the idea of honouring trust responsiveness which enables us to consider the issue of mutuality in trustrelationships. In a second step, we move on to the concept of mutual trust (which is more than some degree of mutuality in a trust relationship), where each individual can be both trustor and trustee. This aspect is visualized within the two-person optimal intertemporal consumption choice model.The corresponding creditor-debtor-game reproduces the well known prisoner's dilemma. In a third step we analyse in depth how the intertemporal elasticity of substitution is related to trust and trust worthiness in (inter)national credit contracts. The fact that we observe multiple creditor-debtor-relationships in an economy seems to reflect not only the gains from cooperation in repeated games, but also the existence of generalized trust in the society.
Keywords: D23; D69; K12; 330; trust; psychological game theory; intertemporal consumption; Vertrauen; Wiederholte Spiele; Wirtschaftspsychologie; Kredit; Gläubiger; Konsumtheorie; Zeitpräferenz; Theorie